2008
DOI: 10.1101/gad.454408
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin promotes the terminal differentiation of embryonic muscle progenitors

Abstract: Myostatin, a TGF-␤ family member, is an important regulator of adult muscle size. While extensively studied in vitro, the mechanisms by which this molecule mediates its effect in vivo are poorly understood. We addressed this question using chick and mouse embryos. We show that while myostatin overexpression in chick leads to an exhaustion of the muscle progenitor population that ultimately results in muscle hypotrophy, myostatin loss of function in chick and mouse provokes an expansion of this population. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
127
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(147 citation statements)
references
References 39 publications
10
127
0
4
Order By: Relevance
“…Intriguingly, the cell-cycle regulator p21 and Myostatin (Mstn), both of which inhibit myoblast proliferation (4, 41-50), were significantly up-regulated in 4OH-Ttreated cells (Table S1). Myostatin is necessary for the balance between proliferation and differentiation of muscle progenitors embryonically and postnatally (41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Myostatin signaling activates expression of p21, inhibiting myoblast proliferation (41)(42)(43)(48)(49)(50)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, the cell-cycle regulator p21 and Myostatin (Mstn), both of which inhibit myoblast proliferation (4, 41-50), were significantly up-regulated in 4OH-Ttreated cells (Table S1). Myostatin is necessary for the balance between proliferation and differentiation of muscle progenitors embryonically and postnatally (41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Myostatin signaling activates expression of p21, inhibiting myoblast proliferation (41)(42)(43)(48)(49)(50)).…”
Section: Resultsmentioning
confidence: 99%
“…Mstn is an important regulator of postnatal myogenesis; it is expressed in quiescent satellite cells and inhibits their activation (41,43). It also inhibits myoblast proliferation, inducing differentiation (42,44,(48)(49)(50). Mstn loss-of-function mutations in mice, cattle, and sheep result in dramatically increased muscle mass (57)(58)(59)(60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies in chick and mouse embryos pointed to a context-dependent effect of myostatin, controlling the balance between proliferation and differentiation on muscle progenitors (46). In contrast, recent data indicate that postnatal muscle hypertrophy generated by the lack of myostatin is largely due to hypertrophy of individual fibers and not to satellite cell activity (47).…”
Section: Discussionmentioning
confidence: 99%
“…The myostatin expression pattern is analogous to that observed in adult mammals, where myostatin mRNA levels are higher in fast-glycolytic fibres than in slow ones (CARLSON et al, 1999;MATSAKAS et al, 2006). Based on these results and on the observation that satellite cells express myostatin and are quiescent (MCCROSKERY et al, 2003), it has been suggested that the normal function of myostatin in postnatal muscle is to maintain satellite cells in a quiescent, undifferentiated state (MANCEAU et al, 2008).…”
Section: Discussionmentioning
confidence: 58%